2012
DOI: 10.1093/arclin/acs055
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Apathy for Everyday Functioning Outcomes in Persons Living with HIV Infection

Abstract: Apathy is a relatively common clinical feature of HIV-Associated Neurocognitive Disorders, but little is known about its implications for everyday functioning outcomes. In the present study, we examined the associations between apathy and self-reported instrumental activities of daily living (IADL) and neurocognitive complaints in 75 participants with HIV infection and 52 demographically comparable seronegative comparison subjects. All volunteers completed the apathy subscale of the Frontal Systems Behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 51 publications
10
58
0
Order By: Relevance
“…Individuals with higher levels of apathy reported greater difficulty performing physical functional tasks, more limitation in activities requisite to social roles at home and in the community, and less frequent engagement in social and communal activities. This is consistent with research on patients with stroke, Alzheimer's disease, Parkinson's disease, H untington's disease, and schizophrenia, as weiJ as Kamat et al's (2012) study on individ uals with HIV These findings highlight the potential harmful real-world correlates of apathy and stress the importance of accurate detection and efficacious treatment of apathy in this population. As HIV survival rates continue to increase, research on the long-term neuropsychiatric effects of the disease becomes more crucial.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Individuals with higher levels of apathy reported greater difficulty performing physical functional tasks, more limitation in activities requisite to social roles at home and in the community, and less frequent engagement in social and communal activities. This is consistent with research on patients with stroke, Alzheimer's disease, Parkinson's disease, H untington's disease, and schizophrenia, as weiJ as Kamat et al's (2012) study on individ uals with HIV These findings highlight the potential harmful real-world correlates of apathy and stress the importance of accurate detection and efficacious treatment of apathy in this population. As HIV survival rates continue to increase, research on the long-term neuropsychiatric effects of the disease becomes more crucial.…”
Section: Discussionsupporting
confidence: 88%
“…For example, among patients with stroke, Alzheimer's disease, Parkinson's disease, Huntington's disease, and schizophrenia, apathy is correlated with impairment in activities of daily living (ADL), diminished quality of life, increased burden to care-givers, decreased general health, and poor treatment compliance (Chase, 2011). Among individuals with HJV, one study (Kamat et at., 2012) found higher levels of self-reported apathy to be associated with greater impairment in functioning, and two studies have reported a relationship between apathy and poor medication adherence (Barclay et al, 2007; Rabkin et al, 2000). While this preliminary evidence suggests that apathy is related to functional deficits in HIV-infected individuals, Tate et al (2003) found no association between apathy and quality of life in HIV-positive individuals; thus further research is necessary.…”
mentioning
confidence: 99%
“…(1,2,9) The Mini-Mental State Examination showed that 28.2% of older people with HIV in our study had cognitive deficit, with significant association with female sex and age 60 to 69 years; however, we found few data in the scientific literature with which to compare this result. (12,13) In the assessment of mental health/humor we found that 24.1% of elderly patients had dysthymia (mild depression); of these, most were men age 60 to 69 years. However, this result was not significant.…”
Section: Discussionmentioning
confidence: 94%
“…This result is similar to the adherence found in the literature showing that older people can guarantee significant control of syndrome manifestation and, at the same time, their longevity as HIV-positive individuals. (11)(12)(13) Effectiveness of adherence to antiretroviral therapy shows a borderline reliability of patients in relation to offering treatment as a way to improve quality of life, in addition to the significant relationship between use of antiretroviral therapy and not being affected by an opportunistic disease. (4,8,11) It is believed that despite the viral suppression provided by the antiretroviral therapy, the level of systemic persistent immune activation and inflammation is low.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that the etiology of mood symptoms may differ for younger and older HIV + groups, and that medical comorbidity burden is not a major cause of depression in older HIV + adults when other potential causes are considered (e.g., loss of a partner, reduced independence). Nonetheless, it is important to highlight the role of affective distress in medical co-morbidity burden as mood symptoms (e.g., depression, apathy) have been associated with adverse functional outcomes in HIV, including medication nonadherence, 58 difficulties with everyday activities, 62 and poorer HRQoL, 63 and are amenable to detection and intervention. 64 Thus, effective screening and treatment of mood symptoms, as well as encouraging healthy behaviors that have been utilized in treatment (e.g., exercise 65 ), may help to prevent the development of medical conditions that may result as a consequence of mood related issues and improve the medical health of younger HIV + individuals.…”
Section: Co-morbidities Age and Hrqol In Hivmentioning
confidence: 99%